Development links psychological causes to evolutionary explanations. Issue 2 (29th April 2014) - Fedyk, Mark; Kushnir, Tamar
Abstract Our conscious abilities are learned in environments that have evolved to support them. This insight provides an alternative way of framing Huang & Bargh's (H&B's) provocative hypothesis. To understand the conflict between unconscious goals and consciousness, we can study the emergence of conscious thought and control in childhood. These developmental processes are also central to the best available current evolutionary theories.